THE The Nexus Between Poverty, Education and Economic Growth in Indonesia - Amaluddin Amaluddin (Economics Development Analysis Journal, 2019)
The causal relationship between poverty, education and economic growth has been widely studied in many countries, however, the results of a lot of studies demonstrate a controversial point of view and diverse conclusions which may be caused by differences in methodologies and development policies. The purpose of this study is firstly, to investigate the dynamic causality relationship between education, poverty, and economic growth both in the short and long-run, secondly, to analyze the dynamic response of poverty to shocks of education and economic growth. This study applied the quantitative method approach by using Panel Error Error Correction Model (PVECM). All secondary data was taken from BPS, in the form of panel data of 33 provinces in Indonesia during the period 2010-2018. This study found strong evidence that there was a long-run feedback causality linkage between poverty, education, and economic growth, while in the short-run, only found a bi-directional causality relationship between education and economic growth. The shocks of education and economic growth were responded negatively by the poverty variable, indicating that improving the quality of education and economic growth plays a vital role or has an impact on poverty reduction.